2022
DOI: 10.1002/ehf2.14202
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate control with landiolol hydrochloride in infants with ventricular dysfunction and pulmonary hypertension

Abstract: Aims Sinus tachycardia potentially leads to a deterioration of cardiac function in critically ill infants. The ultrashort‐acting beta‐blocker landiolol hydrochloride is a new pharmacological option for a selective heart rate (HR) control in patients with sinus tachycardia and heart failure. Methods and results This study was a monocentric retrospective medical chart review study at the University Children's Hospital Bonn (Germany) from 01 January 2018 until 30 June 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, a treatment option in neonates with PH and sinus tachycardia as well as MH is selective HR control using beta-blocking agents such as propranolol or landiolol. In a large cohort study, landiolol was shown to effectively and quickly induce HR control in preterm and term neonates with PH and CD [24]. Selective HR control may have manifold beneficial effects in neonates with PH and/or CD: it decreases the myocardial oxygen demand, optimizes ventricular filling in the diastolic phase, optimizes RV-LV coupling, and can improve RV relaxation impairment in terms of PH [35][36][37][38].…”
Section: Postnatal Management Of Ph and CD In Neonates Following Comp...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a treatment option in neonates with PH and sinus tachycardia as well as MH is selective HR control using beta-blocking agents such as propranolol or landiolol. In a large cohort study, landiolol was shown to effectively and quickly induce HR control in preterm and term neonates with PH and CD [24]. Selective HR control may have manifold beneficial effects in neonates with PH and/or CD: it decreases the myocardial oxygen demand, optimizes ventricular filling in the diastolic phase, optimizes RV-LV coupling, and can improve RV relaxation impairment in terms of PH [35][36][37][38].…”
Section: Postnatal Management Of Ph and CD In Neonates Following Comp...mentioning
confidence: 99%
“…As mentioned above, selective HR control with modern beta-blocking drugs such as landiolol or ivabradine is a treatment option in neonates with diastolic and systolic ventricular dysfunction. A possible target range for HR control which should be aimed for in neonates with sustained sinus tachycardia and CD is 150-170 bpm in preterm neonates born at <35 weeks of GA and 130-150 bpm in late-preterm and term neonates [24].…”
Section: Postnatal Management Of Ph and CD In Neonates Following Comp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Landiolol may also be used to control HR in pediatric patients with non-arrhythmic sinus tachycardia, heart failure, and pulmonary hypertension. According to Schroeder et al, landiolol administration is well tolerated and safe in pediatric patients, being able to achieve a quick HR control; it is associated with an improvement in ventricular dysfunction and pulmonary hypertension severity in critically ill infants [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inodilators (milrinone, levosimendan) are the drugs of choice when a failing neonatal myocardium is in real need of support. If catecholamines, especially norepinephrine, are nevertheless administered to maintain sufficient coronary perfusion pressure, this should preferably be done with simultaneous β1-receptor blockade with a highly specific β1-blocker such as landiolol for infusion 9 or oral bisoprolol. 10 Beta1-selective beta-blockers improve hemodynamics by optimizing heart rate, diastolic filling and coronary perfusion time, systemic blood pressure amplitude with additional optimization of the pulmonary/systemic flow ratio and this with almost no side effects, especially without bronchoconstriction due to β2-adrenergic receptor blocking.…”
mentioning
confidence: 99%